A "Esmorga" and "La Parranda" by Eduardo Blanco Amor: Two languages , Two Identities, Two Versions of a Novel - Doucet, Montserrat (Madrygal. Revista de Estudios Gallegos, 2015)
There are several studies about the literary work of Blanco Amor as a bilingual author and narrative self-translator its important legacy. Not from any of these studies specifically but taking from them the most significant for our purposes we intend to show how the choice of a specific language, determines two different novels. To do this we compared various fragments of both novels.
Keywords: A Esmorga; La Parranda; Eduardo Blanco Amor; self-translation; language and identity